2019
DOI: 10.1002/cm.21585
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating mitochondria in neurons: Cytoskeleton as the conductor

Abstract: Mitochondria are crucial to support synaptic activity, particularly through ATP production and Ca2+ homeostasis. This implies that mitochondria need to be well distributed throughout the different neuronal sub‐compartments. To achieve this, a tight and precise regulation of several neuronal cytoskeleton players is necessary to transport and dock mitochondria. As post‐mitotic cells, neurons are highly dependent on mitochondrial quality control mechanisms and several cytoskeleton proteins have been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Playing central roles in regulating these processes are members of the Rho family of small GTPases, including RhoA and Rac (Ras superfamily members), CDC42, and Rho-associated protein kinase (ROCK), which, after activation by various classes of transmembrane receptors (i.e., integrin receptors, receptor tyrosine kinases, and G protein-coupled receptors), integrate and transmit signals to downstream effector proteins involved in orchestrating cytoskeletal dynamics. Although they are not as well studied or appreciated as being critical to cell function (and cell injury) as many other better known biochemical networks, our findings point to parental RHC exerting ubiquitous, functionally, and structurally protective effects on a number of proteins integral to homeostatic cytoskeletal dynamics, 36 including those affecting cell shape and motility, intra- and intercellular protein and vesicular transport and signaling, 37 organelle biogenesis and movement, 38 dendritic plasticity and axon guidance, the formation of filopodia and lamellipodia, and endocytosis/exocytosis.…”
Section: Discussionmentioning
confidence: 86%
“…Playing central roles in regulating these processes are members of the Rho family of small GTPases, including RhoA and Rac (Ras superfamily members), CDC42, and Rho-associated protein kinase (ROCK), which, after activation by various classes of transmembrane receptors (i.e., integrin receptors, receptor tyrosine kinases, and G protein-coupled receptors), integrate and transmit signals to downstream effector proteins involved in orchestrating cytoskeletal dynamics. Although they are not as well studied or appreciated as being critical to cell function (and cell injury) as many other better known biochemical networks, our findings point to parental RHC exerting ubiquitous, functionally, and structurally protective effects on a number of proteins integral to homeostatic cytoskeletal dynamics, 36 including those affecting cell shape and motility, intra- and intercellular protein and vesicular transport and signaling, 37 organelle biogenesis and movement, 38 dendritic plasticity and axon guidance, the formation of filopodia and lamellipodia, and endocytosis/exocytosis.…”
Section: Discussionmentioning
confidence: 86%
“…All INF2 CMT mutations are predicted or have been shown to increase actin assembly ( Bayraktar et al, 2020 ). While some actin-binding motor proteins likely facilitate microtubule-independent mitochondrial transport, numerous studies have shown that long-range microtubule-based mobility of mitochondria is antagonized by actin and actin-binding motor proteins ( Chada and Hollenbeck, 2004 ; Quintero et al, 2009 ; Pathak et al, 2010 ; Venkatesh et al, 2019 ; Cardanho-Ramos et al, 2020 ). Thus, while the effects of INF2 CMT mutations have yet to be studied in neurons, it is reasonable to expect that INF2 CMT mutations will cause an actin-dependent decrease in mitochondrial mobility in axons.…”
Section: Cmt Mutations Largely Affect Mitochondrial Mobilitymentioning
confidence: 99%
“…While not as well studied or appreciated as critical to cell function (and cell injury) as many other better known biochemical networks, our findings point to parental RHC exerting ubiquitous, functionally and structurally protective effects on a number of proteins integral to cytoskeletal dynamics (31), including those affecting cell shape and motility, intra-and inter-cellular protein and vesicular transport and signaling (32), organelle biogenesis and movement (33), dendritic plasticity and axon guidance, the formation of filopodia and lamellipodia, and endocytosis/exocytosis. We also provided proteomic detail regarding the proteins involved in the multi-pronged defense against systemic-level inflammatory and immune aspects of retinal ischemic injury, revealing 'night-and-day' differences in the expression of major acute phase response proteins (26) in the ischemic retinae of mice born to RHC-treated parents relative to retinae of mice descendant from untreated control parents.…”
Section: Resultsmentioning
confidence: 82%